Motivasi Perawat Pelaksana dan Supervisi terhadap Pendokumentasian Asuhan Keperawatan di Ruang Interna Rumah Sakit Umum Daerah Bobong: Motivation of Implementing Nurses and Supervision of Documenting Nursing Care in the Internal Room at Bobong Regional General Hospital - Abdul Rachman, Darmawati; Dian Ellina , Agusta (Chakra Brahmanda Lentera Institute, 2024)
Work motivation greatly affects the quality of work owned by each individual nurse. Objective: To identify the problem of motivation of implementing nurses and supervision of the documentation of nursing care in the inpatient room of the Bobong Regional General Hospital. Analysis of nurses' work motivation is very important to be evaluated, this is because nurses' motivation is a catalyst to move, namely the desire for encouragement or impulse in the individual as a source of strength to trigger someone to move forward for a goal. The assessment was carried out using a SWOT laying diagram to prioritize strategies that will be implemented to overcome existing problems, this residency intervention plan is to increase work motivation and implement the morning monitoring program of nurses supervise continuously/periodically in standard regulations so that nursing documentation can run optimally. Intervention plan in the residency for the implementation of activities to identify nurses' work motivation and supervise nursing documentation. to know the variables, which are strengths, weaknesses, opportunities and threats and to know the strategies that can be taken by the Bobong Hospital treatment room. Implementation of residency activities. Knowing the variables that are strengths, weaknesses, opportunities and threats as well as to find out the strategies that will be taken by the Bobong Hospital treatment room. Evaluation of the implementation of Identification of nurse motivation towards nursing documentation. knowing the variables which are strengths, weaknesses, opportunities and threats as well as strategies that will be taken by the Bobong Hospital Treatment Room.